Predictive value of integrated 18F-FDG PET/MRI in the early response to nivolumab in patients with previously treated non-small cell lung cancer. Issue 1 (28th April 2020) - Umeda, Yukihiro; Morikawa, Miwa; Anzai, Masaki; Ameshima, Shingo; Kadowaki, Maiko; Waseda, Yuko; Shigemi, Hiroko; Tsujikawa, Tetsuya; Kiyono, Yasushi; Okazawa, Hidehiko; Ishizuka, Tamotsu
Abstract : Background: The early response to treatment with immune-checkpoint inhibitors is difficult to evaluate. We determined whether changes in integrated [ 18 F]-fluoro-2-deoxy-D-glucose positron emission tomography/MRI ( 18 F-FDG PET/MRI) parameters after the first 2 weeks of antiprogrammed death-1 antibody nivolumab therapy could predict the response of patients with non-small cell lung cancer (NSCLC). Methods: Twenty-five patients with previously treated NSCLC were enrolled prospectively and underwent 18 F-FDG PET/MRI before and at 2 weeks after nivolumab therapy. Changes in maximal standardized uptake value, total lesion glycolysis (ΔTLG) and apparent diffusion coefficient (ΔADC) between the two scans were calculated and evaluated for their associations with the clinical response to therapy. Results: The disease control rate was 64%. Patients with non-progressive disease (non-PD) had significantly decreased TLG, increased ADCmean (ie, negative ΔADCmean ) and lower ΔTLG+ΔADCmean than patients with PD. Among the parameters tested, receiver operating characteristic curve analysis revealed that a cut-off value of 16.5 for ΔTLG+ΔADCmean had the highest accuracy (92%) for distinguishing between patients with non-PD and PD. A ΔTLG+ΔADCmean value <16.5 was significantly associated with longer median progression-free survival (9.0 vs 1.8 months, p<0.00001) and overall survival (23.6 vs 4.7 months, p=0.0001) compared with ΔTLG+ΔADCmean value ≥16.5. A multivariate Cox model revealed that ≥16.5 ΔTLG+ΔADCmean was an independent predictor of shorter progression-free survival (HR 37.7) and overall survival (HR 9.29). Conclusions: A combination of ΔTLG and ΔADCmean measured by integrated 18 F-FDG PET/MRI may have value as a predictor of the response and survival of patients with NSCLC following nivolumab therapy. Trial registration number: UMIN 000020707.